An observational study of the relationship between meaningful use-based electronic health information exchange, interoperability, and medication reconciliation capabilities. Issue 41 (October 2017) - Elysee, Gerald; Herrin, Jeph; Horwitz, Leora I.
Abstract : Abstract: Stagnation in hospitals' adoption of data integration functionalities coupled with reduction in the number of operational health information exchanges could become a significant impediment to hospitals' adoption of 3 critical capabilities: electronic health information exchange, interoperability, and medication reconciliation, in which electronic systems are used to assist with resolving medication discrepancies and improving patient safety. Against this backdrop, we assessed the relationships between the 3 capabilities. We conducted an observational study applying partial least squares-structural equation modeling technique to 27 variables obtained from the 2013 American Hospital Association annual survey Information Technology (IT) supplement, which describes health IT capabilities. We included 1330 hospitals. In confirmatory factor analysis, out of the 27 variables, 15 achieved loading values greater than 0.548 at P  < .001, as such were validated as the building blocks of the 3 capabilities. Subsequent path analysis showed a significant, positive, and cyclic relationship between the capabilities, in that decreases in the hospitals' adoption of one would lead to decreases in the adoption of the others. These results show that capability for high quality medication reconciliation may be impeded by lagging adoption of interoperability and health information exchange capabilities. Policies focused on improving one or more of these capabilities may have ancillary benefits. Abstract : Supplemental Digital Content is available in the text